Pointwise wavelet convergence in Besov and uniformly local Sobolev spaces - M. A. Kon; L. A. Raphael (Հայաստանի ԳԱԱ)
The paper announces new conditions for uniform pointwise convergence rates of wavelet expansions in Besov and uniformly local Sobolev spaces.
Keywords: Mathematics; Science